Simplifying the stratigraphy of time - Zalasiewicz, J; Smith, A; Brenchley, P; Evans, J; Knox, R; Riley, N; Gale, A; Gregory, F; Rushton, A; Gibbard, P; Hesselbo, S; Marshall, J; et al. (2004)
We propose ending the distinction between the dual stratigraphic terminology of time-rock units (of chronostratigraphy) and geologic time units (of geochronology). The long-held, but widely misunderstood, distinction between these two essentially parallel time scales in stratigraphy has been rendered unnecessary by the widespread adoption of the global stratotype sections and points (GSSP-golden spike) principle in defining intervals of geologic time within rock strata. We consider that the most appropriate name for this stratigraphic discipline is "chronostratigraphy," which would allow "geochronology" to revert to its mainstream and original meaning of numerical age dating. This in turn makes the little-used formal term "geochronometry" redundant. The terms "eonothem," "erathem," "system," "series," and "stage" would become redundant, in favor of "eon," "era," "period," "epoch" and (disputably) "age." Our favored geologic time units may be qualified by "early" and "late," but not by "lower" and "upper." These suggested changes should simplify stratigraphic practice, encompass both stratified and nonstratified rocks, and help geologic understanding, while retaining precision of meaning.